DIGITAL BRANDING DALAM MENINGKATKAN OMZET PENJUALAN UMKM DI DESA MANGUNAN - Nandhy Wahyuning Arum; Lailatul Izzah; Anang Rohmad Jatmiko; Linda Ratna Sari; Tarrisma Delvy Andini; Ainun Ismayantik; Iftakhul Farikhah; Rifat Maulana Akhbar (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
In the digital era, branding has a major role in increasing brand value, especially for Micro, Small and Medium Enterprises (MSMEs). Digital branding, through the use of social media, websites and applications, has become an effective modern marketing strategy. However, many MSMEs, especially in Mangunan Village, face challenges in implementing digital branding due to a lack of digital understanding and skills, especially for those aged 50 years and over. This community service aims to provide an understanding of digital branding and increase the sales turnover of MSMEs in Mangunan Village through seminars on using the Google My Business application. It is hoped that the results of this activity can help MSMEs create a positive brand image, increase consumer trust, and expand market reach in the digital era. The methods used are surveys, interactive seminars, discussions and personal mentoring. The results show that the majority of MSMEs in Mangunan Village have diverse business potential, but are hampered by age and a lack of understanding of digital technology. This seminar succeeded in increasing participants' knowledge and skills in utilizing digital media to increase sales turnover and branding of their business.